A case study of the depth of fresh/ Salt water interface using values of freshwater heads in groundwater of variable density (2012)
"Almost two thirds of the world's population lives within 400 km of the ocean shoreline; just over half live within 200 km, an area only taking up 10% of the earth's surface. As the world's population continues to grow at an alarming rate, fresh water supplies are constantly being depleted, bringing with it issues such as saltwater intrusion and increasing the importance of groundwater monitoring, management, and conservation. Constant monitoring of the fresh/salt water interface is necessary for proper management of ground water resources. This work studies the variation in the depth of fresh/salt water interface using different values of freshwater heads extracted from heads in coastal groundwater system near The Hague, Netherlands along sections P-DD. Results showed that high density difference between freshwater and saltwater has little effect on the depth of fresh/saltwater interface."